2014
DOI: 10.1016/j.patrec.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A robust cost function for stereo matching of road scenes

Abstract: In this paper different matching cost functions used for stereo matching are evaluated in the context of intelligent vehicles applications. Classical costs are considered, like: sum of squared differences, normalized cross correlation or census transform that were already evaluated in previous studies, together with some recent functions that try to enhance the discriminative power of Census Transform (CT). These are evaluated with two different stereo matching algorithms: a global method based on graph cuts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…However, Yang et al applied a bilateral filter (i.e., a type of edge preserving filter) to improve the flattening of edges and to smooth areas near depth discontinuities. Recently, Miron et al [26] tested various matching cost functions in their stereo disparity map algorithms for intelligent vehicle applications. They concluded that the SD algorithm produced the largest error.…”
Section: Squared Differences (Sd)mentioning
confidence: 99%
“…However, Yang et al applied a bilateral filter (i.e., a type of edge preserving filter) to improve the flattening of edges and to smooth areas near depth discontinuities. Recently, Miron et al [26] tested various matching cost functions in their stereo disparity map algorithms for intelligent vehicle applications. They concluded that the SD algorithm produced the largest error.…”
Section: Squared Differences (Sd)mentioning
confidence: 99%
“…By using the combination of multiple single similarity measures into a composite similarity measure, it has been proven to be an effective method to calculate the matching cost [7][8][9][10]. The adaptive multi-cost approach proposed in this work defines a novel multi-cost function to calculate the raw matching score and employs an adaptive window aggregation strategy to filter the cost volume.…”
Section: Initial Disparity Map Estimationmentioning
confidence: 99%
“…However, they usually produce less accurate depth values. A wide range of stereo matching algorithms have been proposed and their performance has been examined in various surveys [1,2]. A stereo matching algorithm can be performed in four major steps : cost computation, cost aggregation, disparity computation and disparity refinement [3].…”
Section: Introductionmentioning
confidence: 99%